2008
DOI: 10.1007/s10350-007-9152-9
|View full text |Cite
|
Sign up to set email alerts
|

Extended Radical Resection: The Choice for Locally Recurrent Rectal Cancer

Abstract: Resection for recurrent rectal cancer results in good survival with acceptable morbidity, unaffected by the extent of resection. Extended radical resection to obtain clear resection margins is the appropriate management of locally recurrent rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
170
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(192 citation statements)
references
References 31 publications
17
170
2
3
Order By: Relevance
“…Third, the follow‐up duration was relatively short. Although we thought that LR would generally be identified within 3 years after surgery35, 36, 37 and some RCT were also designed to compare the OS, DFS, or LR at this time point,6, 38, 39 longer follow up is required to confirm these results. We plan to follow up this cohort until 5 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the follow‐up duration was relatively short. Although we thought that LR would generally be identified within 3 years after surgery35, 36, 37 and some RCT were also designed to compare the OS, DFS, or LR at this time point,6, 38, 39 longer follow up is required to confirm these results. We plan to follow up this cohort until 5 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Local excision was specified as the primary surgical treatment in 13 studies; 2 of them 26,35 exclusively included patients who had undergone local excision, and the median local excision rate was 10% (range 6%-30%) in the remaining 11 studies. 4,7,17,20,25,29,34,40,44,45,47 Included patients had undergone EBRT as part of the primary treatment in a median of 28% (range 0%-100%) of cases in 43 studies (Table 1). Previous radiotherapy dose was specified in 10 studies, 4,7,9,12,19,27,28,41,55,57 with a total dose ranging from 10 to 110 Gy.…”
Section: Therapy For Primary Rectal Cancermentioning
confidence: 99%
“…Radiotherapy dose was specified in 28 studies. [3][4][5][6][7][8][9]11,18,19,28,29,30,[33][34][35][36][37]41,44,46,47,[50][51][52][53]56,57 Without prior EBRT, the total dose was 40-60 Gy in most studies, with an overall range of 15-80 Gy. Conventional fractionation (1.8-2.0 Gy per fraction) was uniformly applied in 13 studies, 3,6,7,9,11,18,19,28,30,36,46,50,52 and selective use of a hypofractionated schedule (fractions of 5 Gy) was described in 2 studies.…”
Section: Perioperative Treatment For Local Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…2 Heriot et al reported morbidity and mortality rates of 27% and 0.6% respectively. 3 These improvements can also be credited to developments in intraoperative and perioperative treatments, including a better patient selection, the routine use of prophylactic antibiotherapies, venous thromboembolism prevention, anesthesia monitoring, and the use of surgical devices such as the LigaSure TM vessel sealer and divider (Impact TM and Small Jaw TM ), which facilitates the dissection, reduces the blood loss, and shortens the surgical time. 4 Pelvic exenteration is an ultra-radical procedure characterized by en bloc resection of the pelvic organs and can be described on the three axes of the pelvis: antero-posterior, transversal and vertical.…”
Section: Introductionmentioning
confidence: 99%